Socio-economic impacts of solar energy technologies for sustainable green energy: A review - Abdalla, Ahmed N.; Jing, Wang; Nazir, Muhammad Shahzad; Jiang, Mingxing Xin; Tao, Hao (Springer Science and Business Media B.V., 2022)
Although fossil fuels leave environmentally hazardous gases like carbon dioxide, to date, global energy production is mostly dependent on these sources. Depletion of fossil resource and changes in the price make it a major concert for the sustainable use in future and utilization of energy resources which is environmentally safe and sustainable. Therefore, an increase in the use natural sustainable energy like solar power observed to be increased recently. Effective use of solar energy depends on the proper knowledge on its use and techniques. This article reviews different solar storage technologies to obtain green sustainable energy generation. We discussed the variation, mechanism, effectiveness, and worth of greenhouse for solar heat storage and concentrated solar power technologies (CSP). The multi-level evaluation method establishes an evaluation index system, adopts the expert scoring method to determine the weight and score of the index, and combines qualitative and quantitative to obtain a comprehensive evaluation value. There is the evaluation of the socio-economic impact of the green power station construction. The detail of for socio-economic environmental factor for on large-scale operation applications dependence on the use and conditions both solar storage and technologies have advantage and disadvantages. Finally, directions for significant of waste to energy for safe environment are presented.